The influence of piston materials on combustion process in internal combustion engines - Victor Rodionovich Vedruchenko; Alexander Leonidovich Ivanov; Vadim Andreevich Borisov; Pavel Vasil'evich Litvinov (Вестник СибАДИ, 2017)
In this article we are produce an overview of currently existing types of piston internal combustion engines. The analysis of the impact of the piston on the material temperature in the cylinder and the combustion process. The variants of the use of different types of pistons in internal combustion engines, the relevant environmental class Euro. The formulas whose parameters are modified using various types of coatings. The chemical combustion processes using catalytic materials. Conclusions about the possible changes in the methods of calculation of the combustion process.